Applications of Differentiated Instruction for Primary Mathematics Classrooms : A Case Study of Finnish Teachers - Bang, Yeajin (fi=Turun yliopisto|en=University of Turku|, 2018)
Differentiated instruction is implemented by many educators to provide a wide range of avenues for learning to meet each student’s diverse needs. This in-depth case study explores Finnish teachers’ applications and practices of differentiated instruction for primary mathematics classes. For this study, four Finnish primary school teachers, identified as being high implementers of differentiated instruction based on preliminary observations, were participated. Pre and post interviews, observational data, and documents were collected and qualitative content analysis was conducted to interpret the data. The findings of this study indicate that the teachers believed differentiated instruction is effective to foster student learning and to establish equity in education. Such perspectives led the teachers to implement differentiated instruction although they had encountered challenges such as lack of time to prepare and present the lesson, big size class, and insufficient support for competent students. The teachers emphasized frequent and continuous formative assessment to offer the most appropriate learning task within each student’s zone of proximal development. Also, the teachers provided multiple tasks and tiered learning activities with various resources to help all students learn and experience success. Along the way, textbooks played a predominant role to differentiate content and process. The teachers, however, differentiated product less frequently because they were concerned about having fair assessment and grading system. Lastly, flexibility and student autonomy in learning process and learning environment were regarded as important factors to build successful differentiated classrooms. A comparative study that examines differentiated instruction strategies of teachers for primary mathematics classrooms in diverse contexts and more experimental studies to investigate the impact of differentiated instruction on students’ growth and outcomes are suggested for future research.